Improving The Communities Knowledge and Skills about Recognition Of Sports Injuries And The RICE Technique - Dewi Aryanti; Tetik Nurhayati; Sofia Februanti (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The socialisation activity of sports injuries for aerobics instructors is based on the understanding that aerobics is a form of physical activity that can provide significant health and fitness benefits but still has a risk of injury. Sports injuries include overuse and overload of muscles. The purpose of the Community Service (PKM) activity is to explain the types of sports injuries in detail to aerobics instructors and gymnastics participants in the city of Tasikmalaya; educate aerobics instructors and gymnastics participants about the importance of understanding the types of sports injuries and their treatment; provide practical knowledge on how to apply the RICE technique in handling sports injuries. The PKM activity begins with preparing the material: making clear material (in the form of leaflets) regarding the types of sports injuries and the application of the RICE technique as well as educational videos related to the theme. The activity methods include group socialization, namely holding a socialization session in the form of a group meeting with aerobics instructors and gymnastics participants. This session involves the presentation of material on the types of sports injuries that are often experienced and interactive discussions to answer questions and clarify concepts that may arise. Next, Practical demonstration: Presenting practical examples of how to apply the RICE technique in the management of sports injuries.